Political Violence and Language Endangerment in Colombia - Meernik, James David (Terrorism and political violence, 2023)
This paper develops an account of the relationship between language endangerment and conflict violence by combining insights from the fields of political science and linguistics. We develop a theoretical account of the manner in which the violence and disruption of community life jeopardizes the viability of communities that speak endangered languages. Our goals for this paper are to synthesize the contributions linguists and political scientists have made to the study of language endangerment and political violence; develop a theoretical account of language endangerment; and utilize statistical analysis to correlate factors related to political conflict and violence with language endangered communities. We test our theoretical model on language endangerment across the municipalities of Colombia and find support for our hypotheses.